Deciphering the assembly process of PQQ dependent methanol dehydrogenase - Haichuan Zhou; Junqing Sun; Jian Cheng; Min Wu; Jie Bai; Qian Li; Jie Shen; Manman Han; Chen Yang; Liangpo Li; Yuwan Liu; Qichen Cao; et al. (Nature Communications)
Abstract Pyrroloquinoline quinone (PQQ)-dependent methanol dehydrogenases (MDHs), the periplasmic metalloenzymes in Gram-negative methylotrophic bacteria, play a pivotal role in methane and methanol bio-utilization. Although the structures of many PQQ-dependent MDHs have been resolved, including the canonical heterotetrameric enzymes composed of two MxaF and two MxaI subunits with a molecule of PQQ and a calcium ion in the active site in MxaF, the biogenesis of these enzymes remains elusive. Here, we characterize a chaperone, MxaJ, responsible for PQQ incorporation by reconstructing a PQQ-dependent MDH assembly system in Escherichia coli. Using cryo-electron microscopy, we capture the structures of the intermediate complexes formed by the chaperone MxaJ and catalytic subunit MxaF during PQQ-dependent MDH maturation, revealing a chaperone-mediated molecular mechanism of cofactor incorporation. These findings not only advance our understanding on the biogenesis of PQQ-dependent MDH, but also provide an alternative engineering way for methane and methanol bioconversion.